Malocclusions in guinea pigs, chinchillas and rabbits - Legendre, Loïc F.J. (2002)
The types of malocclusions encountered in rodents and lagomorphs are classified. Diagnosis, treatment, and prognosis are reviewed. Some malocclusions are curable, whereas others can only be controlled. The need to perform a complete oral examination and to find a cause for the condition is stressed, as it will seriously affect the prognosis.